THE EFFECT OF BIG BOOK AS A MEDIA ON STUDENTS’ READING COMPREHENSION AT FOURTH GRADE OF ELEMENTARY SCHOOL IN SD LABORATORIUM UNDIKSHA IN ACADEMIC YEAR 20016/2017 - ., Luh Putu Ayu Wijayanti; ., Prof. Dr. Ni Nyoman Padmadewi, M.A.; ., Ni Wayan Surya Mahayanti, S.Pd.,M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh yang signifikan terhadap pemahaman bacaan siswa yang diajar dengan menggunakan buku besar dan mereka yang diajar oleh media konvensional. Rancangan penelitian penelitian ini adalah Quasi Experimental of Posttest Only Control Group Study. Populasi penelitian ini adalah siswa kelas IV SD Laboratorium Undiksha Singaraja. Dua kelas digunakan sebagai sampel penelitian ini. Mereka ditugaskan sebagai kelompok eksperimen dan kelompok kontrol dengan undian. Data yang diperoleh kemudian dianalisis secara deskriptif dan inferensial. Dari hasil penelitian, dapat diketahui bahwa, skor rata-rata kelompok eksperimen adalah 83,56 sedangkan skor rata-rata kelompok kontrol adalah 76,19. Hasil uji-t juga menunjukkan bahwa t-diamati melebihi nilai t-kritis (4,088> 2,042). Dengan demikian, hipotesis nol ditolak, artinya ada pengaruh signifikan dari buku besar sebagai media pembacaan bacaan siswa kelas IV SD SD Undiksha Singaraja.Kata Kunci : Big Book, Pemahaman membaca, Pelajar Pemula This study aimed at investigating whether or not there was any significant effect on students’ reading comprehension who were taught by using big book and those who were taught by conventional media. The research design of this study was Quasi Experimental of Posttest Only Control Group Study. The population of this study was fourth grade students of SD Laboratorium Undiksha Singaraja. Two classes were used as the sample of this study. They were assigned as experimental group and control group by lottery. The obtained data were then analyzed descriptively and inferentially. From the results, it can be seen that, the mean score of the experimental group was 83.56 while the mean score of the control group was 76.19. The result of the t-test also showed that the t-observed exceeded the t-critical value ( 4.088 > 2.042 ). Thus, the null hypohesis was rejected, which means that there was significant effect of big book as a media on students’ reading comprehension at fourth grade of elementary school in SD Laboratorium Undiksha Singaraja.keyword : Big Book, Reading comprehension, Young learners